Surface interaction characterisation of microbial fuel cell organism Shewanella oneidensis. - Maia Kierann Shah (2011)
In order to develop MFCs to their full potential, the mechanisms by which organisms such as S. oneidensis transfer electrons extracellularly need to be researched and understood, and key to this are the physical and chemical interactions between the cell surface and the surrounding environment, including other cells, minerals and MFC-relevant substrates. The research presented here characterises the physical interactions of anaerobically grown S. oneidensis MRl under varying chemical conditions, using aerobically grown cells in identical experiments for comparison. An array of experimental methods are used, including techniques for estimating cell concentration for growth profiles, zeta-potential of cells in solution, and Atomic Force Microscopy imaging of cells in different growth phases. A novel method using Surface Plasmon Resonance is used to quantify the kinetics of binding of cells to surfaces approximating MFC electrodes. This method is assessed for suitability and reviewed as a potential answer to other research problems based on cell-device interfaces. Finally, novel force spectroscopy using custom-made mineral probes is used to gather mechanical data about cells of S. oneidensis MR-1 and to quantify the interaction of cells with iron oxide and graphite. The results show the differences in growth profiles between aerobically and anaerobically grown cells. Different results were also seen for aerobically grown and anaerobically grown cells in preliminary SPR studies using poly-L-lysine, and in the force spectroscopy results including adhesion force and Young's moduli. The effects of pH and salinity on cell surface interaction were investigated using measured isoelectric points from the zeta-potential studies as a guide and found to change the measured values of Young's modulus, and the maximum change in SPR response, for both types of cell. The demonstrable effects of ambient chemistry on cell-cell and cell-surface interaction provide a reference point for bio-device design with the potential for multi-organism devices utilising the multiple electron transfer pathways of S. oneidensis MRl. The use of SPR for real time measurement of whole-cell binding to electrode-approximating surfaces and the resultant interaction kinetics is established as a novel, repeatable and accessible way of investigating cell-surface interaction.